4E analyses and multi-objective optimization of a solar-based combined cooling, heating, and power system for residential applications. (November 2021) - Karim, Sarkhel H. Taher; Tofiq, Tofiq Ahmed; Shariati, Mortaza; Nikafshan Rad, Hima; Ghasemi, Amir
Abstract: The purpose of this paper is to propose a novel combined cooling, heating, and power generation system driven by evacuated tube solar collectors for residential applications. Accordingly, evacuated tube collectors are employed to provide sufficient heat for cooling and power generation purposes, while the waste heat of the evacuated tube collectors is then exploited for heating. The proposed system is comprehensively analyzed from various standpoints i.e., energy, exergy, and exergoeconomic. Afterward, the multi-objective genetic algorithm optimization – as a suitable tool – is applied to the system to extract a trade-off between the competing objective functions. The results showed that R124 results in better exergetic efficiency compared to other refrigerants. The parametric study outcomes indicate that with increasing the collector area, total product cost reduces but the total cost rate increases dramatically. The results also show that input parameters can directly affect the exergetic sustainability index to be cautiously designed. The optimization results show that the system's maximum exergy efficiency is 10.06% while the minimum total cost rate is obtained as 0.4835 $/h. Further, the decision factors' scatter plots show that LiBr mass fraction should be around 25% for optimal operation. Overall, the proposed system can be employed for cooling, heating, and power generation as a potential cycle. Highlights: An innovative CCHP system is proposed. The system is evaluated from energy, exergy, exergoeconomic and exergetic sustainability. Multi-objective optimization is used to find the optimum points of system variables. The optimal exergy efficiency and cost rate of the system are 10.06% and 0.4835 $/h.